MO178DOES OBTAINING AN EXTRA CORE KIDNEY BIOPSY FOR RESEARCH PURPOSES INCREASE THE RISK OF COMPLICATIONS? A SINGLE CENTER EXPERIENCE. (29th May 2021) - Bermejo Garcia, Sheila; García Carro, Clara; Agraz, Irene; Mast, Richard; Vergara, Ander; León, Juan Carlos; Bolufer, Mónica; Seron Micas, Daniel; Soler Romeo, Maria Jose
Abstract: Background and Aims: Kidney biopsy (KB) is the "gold standard" to diagnose nephropathies in our renal patients and it is a procedure with a low rate of complications. Obtaining material for kidney biopsy biobank requires the extraction of one more renal cylinder. The main objective of our study is to analyze the characteristics of a cohort of patients with KB, the safety of the establishment of a renal biopsy biobank with the objective to obtain at least one core of kidney biopsy for research purposes. Method: Observational and prospective study of kidney biopsies performed in our center from January 2019 and 2020. We started a collection of kidney biopsy samples to obtain a biobank at January 2019. Therefore, in patients who accepted, instead of two cylinders, three cylinders were obtained during the procedure when possible. Clinical and laboratory data of the patients were reviewed and we looked for risk factors for complications, including the number of cylinders obtained in the procedure. Results: We reviewed a cohort of 221 patients in whom we performed a kidney biopsy at our hospital. Eight patients (3.6%) underwent trans-jugular renal biopsy, which we have eliminated from the analysis. Of the remaining 213, 126 (59.2%) were men, the mean age was 56.8 (± 16.9) years, 122 (57.3%) patients had hypertension, 46 (23%) were diabetics, 14 (6.5%) were under anticoagulant treatment and 35 (16.4%) were under antiplatelet treatment. Regarding the analytical values, the mean creatinine was 2.22 (± 1.9) mg / dl, protein / creatinine urine ratio 1119.6 [448.3-2957.9] mg / gr, 44.6% (n = 95) had microhematuria, the median hemoglobin pre-KB was 12.1 (± 2.3) g / dL, 254380 (± 8873) platelets, INR 0.98 (± 0.09), prothrombin time of 11.8 (± 1.16) seconds, systolic blood pressure was 135 (± 24.3) mmHg, diastolic blood pressure was 76 (± 15.5) mmHg. The median kidney size was 11 (± 1.23) cm and cortical size was 1.7 (± 0.65) cm. In 113 (53.1%) patients the right kidney was biopsied. 69.5% (n = 148) of the patients 3 renal sample cylinders were obtained, 27.2% (n = 58) 2 cylinders and in 3.3% (n = 7) one cylinder. We did not found differences regarding of renal and cortical size in the patients according to the number of cylinders obtained. We observed that patients in whom 3 cylinders were had a higher percentage of renal biopsy in the left kidney (p = 0.028). We evidenced minor complications in 13.6% (n = 29) and 3.3% (n = 7) major complications. Patients with complications in KB were older (p = 0.039) and had a higher INR (p = 0.031). Patients with one renal cylinder Jin KB, presented a higher percentage of complications with 57.1% vs 17.2% two cylinders and 14.9% with three cylinder (p =0.014). We did not find differences in terms of complications according to the laterality of kidney biopsy (right vs left). Conclusion: Kidney biopsy is a procedure with a low complication rate. Obtaining three renal biopsy cylinders for biobank has not shown an increase in the rate of complications, which remains similar than previously published reports. Our results suggest that the complications are observed mainly in the first and/or second cylinder, and in that case the third core is not performed.